Optimization of EDTA enhanced soil washing on multiple heavy metals removal using response surface methodology - He, Liwei; Li, Bin; Ning, Ping; Gong, Xiao (Journal of Environmental Engineering and Landscape Management, 2018)
This research presents the optimization of soil washing conditions in the removal of multiple heavy metals (Cu-Pb-Zn-Cd) under the using of ethylenediaminetetraacetic acid (EDTA). The optimum combination of washing parameters in a bench-scale soil washing experiments is determined by response surface methodology (RSM). Central composite design is applied after single factor experiment, EDTA concentration, solid-to-liquid ratio and washing time are evaluated variables for the removal processes, and the regression models of HMs are constructed. The results show that, EDTA concentration and solid-to-liquid ratio are significant factors for this process. Subsequently, 50% of Cu removal was set as the optimum target to optimize the combined conditions, through the building of multiple quadratic regression models, the optimal condition combination is determined that EDTA concentration is 0.0026 mol·L-1, solid-to-liquid ratio is 1:22, washing time is 3.89 h, the extraction rate of Pb, Zn, Cd is predicted to be 78%, 75% and 71%, respectively.